2010
DOI: 10.1149/1.3483550
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Methods for Detecting and Characterizing Voids in Bonded Wafer Pairs

Abstract: The Wafer Bond Task Force of the SEMI MEMS Standards Committee has begun a round robin experiment to evaluate methods for identifying and characterizing voids in bonded wafer pairs for three-dimensional integrated circuit (3D IC) applications. Due to the numerous process steps that the wafers have undergone and the presence of Through-Silicon Vias (TSVs), bonded wafers containing 3D ICs are expected to suffer a higher rate of postbonding voids than other bonding applications. In addition, 3D ICs will likely be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…SEMI draft document 5270 is being developed to provide a guide to the metrology tools that identify and characterize voids between bonded wafers. A number of tools have been identified that are capable of detecting and/or characterizing bond voids, and a round robin experiment is currently underway to provide a guide to the capabilities and limitations of each of these tools (5).…”
Section: Bond Voidmentioning
confidence: 99%
“…SEMI draft document 5270 is being developed to provide a guide to the metrology tools that identify and characterize voids between bonded wafers. A number of tools have been identified that are capable of detecting and/or characterizing bond voids, and a round robin experiment is currently underway to provide a guide to the capabilities and limitations of each of these tools (5).…”
Section: Bond Voidmentioning
confidence: 99%
“…Since silicon and other semiconductor materials, while opaque to visible light, are relatively transparent to NIR wavelengths longer than 1100 nm [7][8][9], it is possible to inspect within and beneath semiconductor materials in a non-destructive way without cross-sectioning or otherwise disrupting the samples. NIR microscopy is widely used in the semiconductor industry, especially in 3D packaging technologies, for inspecting subsurface defects and structures of semiconductor and microelectro-mechanical system (MEMS) devices [1,6,7,10]. Also, the NIR imaging technique can be used during the manufacturing process, such as during overlay alignment, to improve the TSV quality and to achieve the required 3D stack yields.…”
Section: Introductionmentioning
confidence: 99%